Usability of a Low-Cost Head Tracking Computer Access Method following Stroke. - Mah, Jasmine; Jutai, Jeffrey W.; Finestone, Hillel; Mckee, Hilary; Carter, Melanie (Assistive Technology)
Assistive technology devices for computer access can facilitate social reintegration and promote independence for people who have had a stroke. This work describes the exploration of the usefulness and acceptability of a new computer access device called the Nouse™ (Nose-as-mouse). The device uses standard webcam and video recognition algorithms to map the movement of the user’s nose to a computer cursor, thereby allowing hands-free computer operation. Ten participants receiving in- or outpatient stroke rehabilitation completed a series of standardized and everyday computer tasks using the Nouse™ and then completed a device usability questionnaire. Task completion rates were high (90%) for computer activities only in the absence of time constraints. Most of the participants were satisfied with ease of use (70%) and liked using the Nouse™ (60%), indicating they could resume most of their usual computer activities apart from word-processing using the device. The findings suggest that hands-free computer access devices like the Nouse™ may be an option for people who experience upper motor impairment caused by stroke and are highly motivated to resume personal computing. More research is necessary to further evaluate the effectiveness of this technology, especially in relation to other computer access assistive technology devices.